2016
DOI: 10.1101/lm.042895.116
|View full text |Cite
|
Sign up to set email alerts
|

Memory trace reactivation and behavioral response during retrieval are differentially modulated by amygdalar glutamate receptors activity: interaction between amygdala and insular cortex

Abstract: The insular cortex (IC) is required for conditioned taste aversion (CTA) retrieval. However, it remains unknown which cortical neurotransmitters levels are modified upon CTA retrieval. Using in vivo microdialysis, we observed that there were clear elevations in extracellular glutamate, norepinephrine, and dopamine in and around the center of the gustatory zone of the IC during CTA retrieval. Additionally, it has been reported that the amygdala-IC interaction is highly involved in CTA memory establishment. Ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…Presentation of the CS for CTA induces marked ERK activation in both the IC and BLA (Berman, 2003;Lin et al, 2010) and activation of BLA projections to reward centers (Inui et al, 2013). However, electrophysiological activity is inhibited in the majority of recorded BLA units in vivo (Uwano et al, 1995;Kim et al, 2010), Nonetheless, electrophysiological and molecular changes within excitatory BLA neurons have indeed been reported in a number of studies examining CTA acquisition and retrieval (Yasoshima and Yamamoto, 2005;Barot et al, 2008;Guzman-Ramos and Bermudez-Rattoni, 2012;Osorio-Gó mez et al, 2017). Perhaps, despite their activation during acquisition, only a small proportion of BLA neurons is reactivated during retrieval, while the contribution of fibers projecting through or away from the BLA is indeed significant (Dunn and Everitt, 1988;Bahar et al, 2004;Inui et al, 2019).…”
Section: Discussionmentioning
confidence: 98%
“…Presentation of the CS for CTA induces marked ERK activation in both the IC and BLA (Berman, 2003;Lin et al, 2010) and activation of BLA projections to reward centers (Inui et al, 2013). However, electrophysiological activity is inhibited in the majority of recorded BLA units in vivo (Uwano et al, 1995;Kim et al, 2010), Nonetheless, electrophysiological and molecular changes within excitatory BLA neurons have indeed been reported in a number of studies examining CTA acquisition and retrieval (Yasoshima and Yamamoto, 2005;Barot et al, 2008;Guzman-Ramos and Bermudez-Rattoni, 2012;Osorio-Gó mez et al, 2017). Perhaps, despite their activation during acquisition, only a small proportion of BLA neurons is reactivated during retrieval, while the contribution of fibers projecting through or away from the BLA is indeed significant (Dunn and Everitt, 1988;Bahar et al, 2004;Inui et al, 2019).…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, unlike blockade of the NMDAR-CaMKIIα effects, CNQX (competitive AMPA/kainate receptor antagonist) microinfusion into the IC 1 h following novel taste learning suppresses CTA retrieval even when the US is delivered 4 h later (Adaikkan and Rosenblum, 2015 ). On the other hand, microinfusion of CNQX into the amygdala disrupts CTA expression and suppresses norepinephrine and dopamine augmentations in the IC (Osorio-Gomez et al, 2016 ). Novel taste learning itself induces up-regulation of the GluR1 AMPAR subunit, while AMPAR trafficking and signaling in the IC influences the ability of long-term memory trace inputs to form negative CS-US associations (Adaikkan and Rosenblum, 2015 ; Osorio-Gomez et al, 2016 ).…”
Section: Aversive Taste Memory Encoding and The Insulamentioning
confidence: 99%
“…On the other hand, microinfusion of CNQX into the amygdala disrupts CTA expression and suppresses norepinephrine and dopamine augmentations in the IC (Osorio-Gomez et al, 2016 ). Novel taste learning itself induces up-regulation of the GluR1 AMPAR subunit, while AMPAR trafficking and signaling in the IC influences the ability of long-term memory trace inputs to form negative CS-US associations (Adaikkan and Rosenblum, 2015 ; Osorio-Gomez et al, 2016 ). AMPAR-dependent activity in the IC might underlie the ability of the brain to encode the aversion expected by a sensory experience and to re-evaluate its relevant weight in predicting the US in relation to inputs arising from the extended taste learning circuit upon subsequent consolidation trials (Eisenberg et al, 2003 ).…”
Section: Aversive Taste Memory Encoding and The Insulamentioning
confidence: 99%
“…Studies have indicated its role in working memory of taste (Ragozzino and Kesner, 1999), conditioned taste aversion (Schier et al, 2016) and taste learning [see review by Yiannakas and Rosenblum (2017)]. This is in part mediated by glutamatergic and dopaminergic transmission (Guzmán-Ramos et al, 2010; Osorio-Gómez et al, 2017), which also showed enrichment in the insula. However, no gene ontology groups corresponding to taste specifically were enriched in the IC.…”
Section: Discussionmentioning
confidence: 99%